ANALYSIS OF INDICATORS DOPLEROMETRICHESKIH IN THE MOTHER-PLACENTA-FETUS IN PREGNANT WOMEN WITH ARTERIAL HYPERTENSION - Макаров, О.Г. (World of Medicine and Biology, 2016)
Ultrasonographic study the definition of systolic ratio, pulsation index and resistance index of uterine artery, uterine spiral arteries, the umbilical artery and middle cerebral artery of the fetus from the 30 healthy pregnant women and 60 pregnant women with various forms of hypertensive states were held. The results suggest the primary lesion matochno- placental circulation link in a vicious circle of pathogenesis of feto-placental insufficiency with hypertension during pregnancy. We established a violation of blood circulation in the utero-placental-fruit complex in 14-18 necessitate doplerometricheskogo studies in pregnant women with hypertension in early pregnancy for the purpose of early diagnosis of disorders of blood circulation, fetal hypoxia and malnutrition, and hence the timely start of treatment.
Keywords: hypertensive status; vascular resistance; doplerometrii; haemocirculation; fetoplacental complex